(untitled) (Research, Society and Development, 2020)
Objective: To analyze the epidemiological profile of people diagnosed with HIV/AIDS. Methods: This is a quantitative study carried out using DATASUS. Gender, age, education, region and race / color of people diagnosed with HIV/AIDS were evaluated individually in the period from 2015 to 2019. Results: Male gender is the most affected by the disease with 69%, the age group is between 25 to 49 years (67% of the total cases). Education 36% of people who were diagnosed with HIV/AIDS incomplete elementary education, 56% did not complete high school, 26% had completed high school, 6% incomplete higher education and 11% completed higher education. The Southeast region was the one that had more cases with 39% of the total and the race / color of these people, was ignored in 76,295 of the records. Thus, only 94,218 were used as 100% of the cases, with the majority being of mixed race (46%). Conclusion: The results of this study reinforce the need for a greater implementation of public policies for the dissemination of knowledge on the prevetion of HIV infection. Thus also preventing AIDS, since the population most affected is low education and young adult men.